2016
DOI: 10.18805/ijar.9420
|View full text |Cite
|
Sign up to set email alerts
|

Egg quality, geometry and hatching traits of indigenous Aseel as influenced by organic and inorganic selenium supplementation

Abstract: This study was conducted to evaluate the impact of selenium sources on egg and hatching traits of native Aseel chicken. Selenium-treated 21-weeks-aged 84 pullets and 12 cockerels from Lakha, Mushki, Peshaweri and Mianwali varieties (21 pullets and 3 cockerels per variety) were divided into three treatment groups A, B and C (7 pullets and 1 cockerel per group). Group A and B were experimental and C was control. Ration for group A was included 0.3 mg/kg Se-yeast, B was included 0.3 mg/kg sodium selenite and C wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…In contrast, no significant (P>0.05) impact of Se was found on final body weight of broilers (Vara et al, 2007;Yoon et al, 2007) Production performance and selenium sources: In a study, it was demonstrated that reproductive traits were improved with the inclusion of Se, while Sel-Plex supplementation improved sperm survival in the oviduct, as well as the production of more settable eggs (Robert et al, 2008). Eggs from breeder hens fed organic Se source had greater Se content than those treated with an inorganic source (Leeson et al, 2008;Zia et al, 2016a). A significant difference was observed in eggs, tissues and hatchability in the Se treated birds than the birds maintained on control diet (Brennan et al, 2011).…”
Section: Effect Of Form Of Selenium In Antioxidative Statusmentioning
confidence: 88%
See 3 more Smart Citations
“…In contrast, no significant (P>0.05) impact of Se was found on final body weight of broilers (Vara et al, 2007;Yoon et al, 2007) Production performance and selenium sources: In a study, it was demonstrated that reproductive traits were improved with the inclusion of Se, while Sel-Plex supplementation improved sperm survival in the oviduct, as well as the production of more settable eggs (Robert et al, 2008). Eggs from breeder hens fed organic Se source had greater Se content than those treated with an inorganic source (Leeson et al, 2008;Zia et al, 2016a). A significant difference was observed in eggs, tissues and hatchability in the Se treated birds than the birds maintained on control diet (Brennan et al, 2011).…”
Section: Effect Of Form Of Selenium In Antioxidative Statusmentioning
confidence: 88%
“…However, some researchers presented a different point of view and reported no correlation between Se and egg weight (Pavlovic et al, 2009). Variation in egg mass is linked with the supplementation of Se forms in the diet as it is evident from certain reports that the inclusion of SY supplementation had significantly improved the egg mass in laying hens (Gjorgovska et al, 2012;Zia et al, 2016a). Many other studies, likewise, showed positive or no effect of different Se forms on FCR/ dozen or FCR/kg egg mass in poultry.…”
Section: Effect Of Form Of Selenium In Antioxidative Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of response to in ovo feeding may depend on genetics, egg size, breeder hen age, and incubation conditions, site of injection and doses (Uni and Ferket ,2003), however Some researchers who demonstrated that selenium sources help in increasing egg production traits as well as hatchability (Attia et al., 2010;Canogullari et al, 2010;Waseem et al, 2016).…”
Section: Introductionmentioning
confidence: 99%